Blunt Ocular Trauma Complicated by Hyphema - Pramanandari, Made Indah (Jurnal Health Sains, 2024)
In this era of industrialization and high-speed traffic, the incidence of trauma is increasing in general. According to research, ocular trauma is also one of the causes of quite high rates of blindness. A male patient, 35 years old, came to the Bhayangkara Denpasar Eye Clinic initially on October 3 2023 with a complaint. The patient complained of pain in the right eye after being hit by a shuttlecock approximately 1 hour before the patient came to the hospital. Complaints are accompanied by red eyes, blurred vision, pain and watering. The patient said he had not received therapy for his complaint. Denied history of complaints of fever, cough, runny nose, shortness of breath. blunt ocular trauma which causes complications of hyphema and secondary glaucoma.